PENGARUH E-SERVICE QUALITY TERHADAP E-LOYALTY PADA INDUSTRI MARKETPLACE INDONESIA - Lili Adi Wibowo; Puspo Dewi Dirgantari; Lunia Nur Larasati (Universitas Pendidikan Indonesia, 2021)
The purpose of this research is to find out the influence of e-service quality on e-loyalty in millennial women followers of Instagram Shopee, Tokopedia, and Bukalapak. A total of 200 respondents were using probability sampling. A questionnaire was used a research instrument to collect data from respondents. The analisis technique used is a verification technique using of structure equation model (SEM). The research shows that e-service quality has an influence on e-loyalty.